Pressure effect on the Fermi surface and electronic structure of LuGa3 and TmGa3 - Pluzhnikov, V.B.; Grechnev, G.E.; Czopnik, A.; Eriksson, O. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
The Fermi surfaces and cyclotron masses of LuGa3 and TmGa3 compounds are studied by means of the de Haas—van Alphen effect technique under pressure. The highly anisotropic pressure dependences of the de Haas—van Alphen frequencies and cyclotron masses have been observed in both compounds. Concurrently, the ab initio calculations of the volume-dependent band structures have been carried out for these compounds, including ferromagnetic configuration phase of TmGa3, by employing a relativistic version of the full-potential linear muffin-tin orbital method within the local spin-density approximation. The experimental data have been analysed on the basis of the calculated volume-dependent band structures and compared with the corresponding pressure effects in the isostructural compound ErGa3.